2004
DOI: 10.1021/la049388s
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical Failure of Soft Acrylic Adhesives under Tensile Stress

Abstract: The mechanisms of failure over time of a series of model acrylic pressure-sensitive adhesives under a moderate level of stress has been investigated with a probe method. Two competing mechanisms of failure have been observed: a progressive nucleation of cavities under stress and the propagation of existing cavities at the interface between the probe and the adhesive layer. Homogeneous creep of the adhesive was never observed as the only failure mechanism. In situations where the resistance to crack propagation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 34 publications
2
38
0
Order By: Relevance
“…When the spring constant is comparable to the elasticity, the limit of K   will give an upper bound for the shift in contact position, although for many experiments such as probe-tack tests 42 , extensional rheology measurements, 43 and more generally measurements with stiff cantilevers and load cells, the K   situation are often encountered.…”
Section: K mentioning
confidence: 99%
“…When the spring constant is comparable to the elasticity, the limit of K   will give an upper bound for the shift in contact position, although for many experiments such as probe-tack tests 42 , extensional rheology measurements, 43 and more generally measurements with stiff cantilevers and load cells, the K   situation are often encountered.…”
Section: K mentioning
confidence: 99%
“…The PZ model is derived based on a force balance at the peel zone and takes into account three forces: the peel force F acting in the peel direction, the adhesion force F ⊥ acting normal to the surface, and the friction/shear force F || acting parallel to the surface. The peel zone is defined as the bifurcation between the tape backing and the surface in which cavitation and fibrillation occur ( Figure 1C) [Zosel, 1989;Zosel, 1998;Créton and Leibler, 1996;Lindner et al, 2004;Shull et al, 2004;Portigliatti et al, 2000]. We assume that the curvature of the tape backing is circular and that the length of the peel zone on the surface is equal to the arc length of the tape backing up to the point of the last fibril or filament.…”
Section: Theorymentioning
confidence: 99%
“…Depending of the tackiness of the adhesive [Zosel, 1989;Zosel, 1998;Créton and Leibler, 1996;Lindner et al, 2004;Shull et al, 2004;Portigliatti et al, 2000], φ o can range from 90 o (large tackiness) to almost 0 o (small tackiness). For peel angles greater than φ o , the shape and dimension of the peel zone remains constant and thus the normal component of the peel force also remains constant.…”
Section: Constant Peel Zone Detachment Modementioning
confidence: 99%
“…[5][6][7][8][9] Following these advances, Lindner and Maevis 10 have studied the failure over time of acrylic PSA layers loaded to the subcritical stress level that does not cause immediate failure. Interestingly, they found that the failure under low load did not occur by a progressive creep of the adhesive but by the nucleation of cavities and their progressive growth.…”
Section: Introductionmentioning
confidence: 99%